2021
DOI: 10.3389/fcell.2020.599048
|View full text |Cite
|
Sign up to set email alerts
|

ATM Kinase-Dependent Regulation of Autophagy: A Key Player in Senescence?

Abstract: Increasing evidence suggests a strong interplay between autophagy and genomic stability. Recently, several papers have demonstrated a molecular connection between the DNA Damage Response (DDR) and autophagy and have explored how this link influences cell fate and the choice between apoptosis and senescence in response to different stimuli. The aberrant deregulation of this interplay is linked to the development of pathologies, including cancer and neurodegeneration. Ataxia-telangiectasia mutated kinase (ATM) i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(30 citation statements)
references
References 64 publications
(89 reference statements)
0
18
0
Order By: Relevance
“…Its reversal by AP20187 treatment suggests that cells expressing the INK-ATTAC cassette and eliminated by the AP20187 treatment are the major responders to the oxidative damage and associated DNA damage. DNA damage is known to induce cellular senescence via cyclin dependent kinase inhibitor genes ( Fischer and Muller, 2017 ; Stagni et al, 2021 ). Indeed Cdkn2B (p15 Ink4b ; Ref.…”
Section: Resultsmentioning
confidence: 99%
“…Its reversal by AP20187 treatment suggests that cells expressing the INK-ATTAC cassette and eliminated by the AP20187 treatment are the major responders to the oxidative damage and associated DNA damage. DNA damage is known to induce cellular senescence via cyclin dependent kinase inhibitor genes ( Fischer and Muller, 2017 ; Stagni et al, 2021 ). Indeed Cdkn2B (p15 Ink4b ; Ref.…”
Section: Resultsmentioning
confidence: 99%
“…Since damaged such organelles need to be removed, autophagy machinery is activated. Many factors cause damage to organelles, and in the case of damage by DNA damaging agents, studies are continuing to show that autophagy is activated to control cell fate to maintain homeostasis in cells (Stagni et al, 2020). ATM, the major sensor of DSB, is involved in generating signal transduction by recognizing the damaged area when DNA damage occurs, and autophagy is activated by this ATM pathway (Eliopoulos et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…In lymphopenic patients a decline of both CD4 + and CD19 + cells was noted, but classical opportunistic infections, as that from Pneumocystis jirovecii, did not occur in our cohort of AT patients, indicating that the quantitative deterioration of these cells does not equate a functional progressive immune deficiency. It has been reported that the loss of ATM expression in AT cells triggers a senescent-like phenotype, including upregulation of genes associated to senescence and cancer, decreased cellular replication capacity, shortening telomeres, and autophagy abnormalities [32][33][34][35]. The progressive immunological deterioration in AT patients, which parallels the neurological impairment, may account for the increased frequency or greater severity of infections with age.…”
Section: Discussionmentioning
confidence: 99%